Chapter 11: Mixed methods practice in operational research: designs for wicked problems - Christie, Jane S. (Edward Elgar Publishing, 2023)
In operational research (OR), practitioners model and analyse real-world issues, and support organizational and policy decision-making. Traditionally, they use quantitative methods, such as optimization, simulation, and statistical analysis. Many also use participative, qualitative modelling methodologies known as problem structuring methods (PSMs), which are particularly suitable for wicked problems. There have been recent, renewed calls for OR practice that integrates PSMs with traditional methods, and for guidance for practitioners, students and organizational clients on how to do it and its benefits. Accordingly, in this chapter, I introduce mixed methods practice and theory in OR, review the prevalence of mixing PSMs with traditional OR, and showcase six methodological designs with examples - typical and innovative - from OR interventions across public, private, and third sector organizations. I describe a range of benefits, including successful engagement with dynamic, social, organizational contexts, and discuss current and future research directions.